2001
DOI: 10.1111/1467-9481.00160
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time changes in the paradigm of personal pronouns in Montreal French

Abstract: Based on the results of three variationist studies on personal pronouns used in Montreal French, this article shows how real-time data can shed light oǹ apparent time interpretation' and increase our understanding of morphosyntactic changes. Longitudinal data for a 24-year period from three corpora of spoken French are used to discuss cases of variation: variation between the clitics on and nous, alternation between on and tu/vous, and variation among non-clitic plural pronouns. While the ®rst case illustrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 11 publications
3
25
0
5
Order By: Relevance
“…Their results suggested that age grading and generational change might not be mutually exclusive. This effect has also been observed by Zilles (2005) and Blondeau (2001) who likewise used both panel and trend approaches. Based on G. Sankoff's 2005 and 2006 reviews of the state of research, these speakers can be divided into two groups: those who are part of the active population and follow in the direction of the change and those who go in the opposite direction.…”
Section: Introductionsupporting
confidence: 69%
“…Their results suggested that age grading and generational change might not be mutually exclusive. This effect has also been observed by Zilles (2005) and Blondeau (2001) who likewise used both panel and trend approaches. Based on G. Sankoff's 2005 and 2006 reviews of the state of research, these speakers can be divided into two groups: those who are part of the active population and follow in the direction of the change and those who go in the opposite direction.…”
Section: Introductionsupporting
confidence: 69%
“…Variation in the pronouns of French has been explored in both Quebec (e.g. Laberge 1977;Thibault 1983;Deshaies 1985;Blondeau 2001) and, to a lesser extent, France (e.g. Ashby 1992;Coveney 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Par ailleurs, les deux approches en temps réel qui s'offrent au chercheur permettent de distinguer ce qui relève du changement individuel (suivi de cohorte) du changement au sein de la communauté (suivi des tendances communautaires). D'autres études récentes adoptant ces deux approches méthodologiques en temps réel ont examiné la contribution individuelle aux changements linguistiques communautaires pour différentes variables, un aspect que la sociolinguistique du français avait peu examiné jusqu'à ce jour (Blondeau, 2001 ;Blondeau et al, 2002 ;Sankoff et al, 2001b). La réflexion méthodologique pré-sentée dans le présent article, tout en se concentrant spécifiquement sur le suivi de cohorte, s'inscrit dans la poursuite de ces avenues de recherche.…”
unclassified